Accompanied by brother to receive BASF Petronas Chemical Excellence Award - Norhidayah, Mohamad (UMPSA, 2024)
The recipient of the Excellence Award of BASF Petronas Chemical Sdn. Bhd. at the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) 18th Convocation Ceremony, Amir Syarifuddin Baharudin, 24, was excited but somewhat saddened when he could not celebrate this special day with his loved ones.